Novel mutations of PKD genes in Chinese patients suffering from autosomal dominant polycystic kidney disease and seeking assisted reproduction - Wen-Bin He; Wen-Juan Xiao; Yue-Qiu Tan; Xiao-Meng Zhao; Wen Li; Qian-Jun Zhang; Chang-Gao Zhong; Xiu-Rong Li; Liang Hu; Guang-Xiu Lu; Ge Lin; Juan Du (BMC, 2018)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD), the commonest inherited kidney disease, is generally caused by heterozygous mutations in PKD1, PKD2, or GANAB (PKD3). Methods We performed mutational analyses of PKD genes to identify causative mutations. A set of 90 unrelated families with ADPKD were subjected to mutational analyses of PKD genes. Genes were analysed using long-range PCR (LR-PCR), direct PCR sequencing, followed by multiplex ligation-dependent probe amplification (MLPA) or screening of GANAB for some patients. Semen quality was assessed for 46 male patients, and the correlation between mutations and male infertility was analysed. Results A total of 76 mutations, including 38 novel mutations, were identified in 77 families, comprising 72 mutations in PKD1 and 4 in PKD2, with a positive detection rate of 85.6%. No pathogenic mutations of GANAB were detected. Thirty-seven patients had low semen quality and were likely to be infertile. No association was detected between PKD1 mutation type and semen quality. However, male patients carrying a pathogenic mutation in the Ig-like repeat domain of PKD1 had a high risk of infertility. Conclusion Our study identified a group of novel mutations in PKD genes, which enrich the PKD mutation spectrum and might help clinicians to make precise diagnoses, thereby allowing better family planning and genetic counselling. Men with ADPKD accompanied by infertility should consider intracytoplasmic sperm injection combined with preimplantation genetic diagnosis to achieve paternity and obtain healthy progeny.